Effects of Remanufacturable Product Design on Market Segmentation and the Environment1. (19th January 2016) - Shi, Tianqin; Gu, Wenjun; Chhajed, Dilip; Petruzzi, Nicholas C.
ABSTRACT: Despite documented benefits of remanufacturing, many manufacturers have yet to embrace the idea of tapping into remanufactured‐goods markets. In this article, we explore this dichotomy and analyze the effect of remanufacturable product design on market segmentation and product and trade‐in prices by studying a two‐stage profit‐maximization problem in which a price‐setting manufacturer can choose whether or not to open a remanufactured‐goods market for its product. Our results suggest that it is optimal for a manufacturer to design a remanufacturable product when the value‐added from remanufacturing is relatively high but product durability is relatively low and innovation is nominal. In addition, we find that entering a remanufactured‐goods market in and of itself does not necessarily translate into environmental friendliness. On the one hand, the optimal trade‐in program could result in low return and/or remanufacturing rates. On the other hand, a low price for remanufactured products could attract higher demand and thereby potentially result in more damage to the environment. Meanwhile, external restrictions imposed on total greenhouse gas emissions draw criticism in their own right because they risk stifling growth or reducing overall consumer welfare. Given these trade‐offs, we therefore develop and compare several measures of environmental efficiency and conclude that emissions per revenue can serve as the best proxy for emissions as a metric for measuring overall environmental stewardship.